Evaluation of the pharmacokinetics of the DPP-4 inhibitor gemigliptin when coadministered with rosuvastatin or irbesartan to healthy subjects. (February 2015) - Choi, Hee Youn; Lim, Hyeong-Seok; Kim, Yo Han; Jeon, Hae Sun; Kim, Mi Jo; Lee, Shi Hyang; Jung, Jong Hyuk; Lee, Young Kyoung; Kim, Hyun Jeong; Bae, Kyun-Seop
Abstract Objective: Gemigliptin is a selective DPP4 inhibitor used to treat type 2 diabetes. The objective of this study was to evaluate the pharmacokinetics (PKs) of gemigliptin, rosuvastatin, and irbesartan monotherapies and combination therapies. Research design and methods: Randomized, open-label, three-treatment, six-sequence, three-period, crossover studies were performed on healthy male volunteers. The three treatments were: 50 mg gemigliptin alone; 20 mg rosuvastatin (part A) or 300 mg irbesartan alone (part B); and rosuvastatin or irbesartan with concomitant gemigliptin. Each drug was administered as part of once daily, 7 day, repeated dosing regimens with a 14 day washout period. Clinical trial registration: NCT01823133 (part A) and NCT01825850 (part B). Main outcome measures: The primary PK parameters – Cmax and AUCτ – were compared to the geometric mean ratios (GMRs) and 90% confidence intervals (90% CIs) that were determined for the combination therapies and monotherapies. Results: A total of 60 participants were administered the study drugs, and 52 participants (27 participants in part A; 25 participants in part B) were analyzed as part of the PK dataset. In part A, the GMRs (gemigliptin + rosuvastatin/gemigliptin) of the Cmax and AUCτ values of gemigliptin were 0.955 (90% CI = 0.874–1.044) and 1.023 (90% CI = 0.991–1.057), and those of rosuvastatin were 1.012 (90% CI = 0.946–1.084) and 1.086 (90% CI = 1.032–1.142), respectively. In part B, the GMRs of the Cmax and AUCτ values of gemigliptin were 1.046 (90% CI = 0.964–1.134) and 1.035 (90% CI = 1.005–1.065), and those of irbesartan were 0.966 (90% CI = 0.897–1.040) and 1.050 (90% CI = 0.993–1.111), respectively. The limitations of this study include its relatively short treatment period and small sample size, as only healthy participants were included. Conclusions: Gemigliptin does not affect the PK properties of rosuvastatin or irbesartan; also, rosuvastatin and irbesartan do not affect the PKs of gemigliptin.